Physical Skills in Male Volleyball Players 14-18 Years Old - Martiri, Altin (European Journal of Multidisciplinary Studies, 2022)
During the monitoring of volleyball teams in Albania during training, it was noticed that coaches pay more attention to technical elements and not to physical abilities to ages 14-18 years. The aim of this study was to find out the trend of improvement and differences with the age on physical abilities of male’s volleyball players in Albania. Methods: Participants in this study were N=43 volleyball players from two age categories; N=21, cadet (14-16 yrs.), N= 22 and junior (16-18 yrs.) Measurement for anthropometrics (body weight, body height) and physical abilities (push up test, curl-up test, standing long jump and vertical jump test) were assessed. Results: Analysis between two age categories shows significant differences. Showed results for anthropometrics and also for physical abilities showed differences between groups of volleyball players. Data of this study for jumping performance using vertical jump CMJ test between groups for cadet vs. junior data show (mean difference= 21.3 cm; Sig= 0.004) while for vertical jump Run up test between groups for cadet vs. junior data show (mean difference= 22.3 cm; Sig= 0.003). Conclusion: In the best interest of the study, it would be good if other teams were involved from different cities of Albania. Suggestions for other studies we recommend in comparing data by positions in the field. Trainers should plan training with these age groups different coordination programs not only technical. This study has limitations with regards to the sampling number of male volleyball players, which is justified for not having sufficient funds.